Moenomycin Biosynthesis: Structure and Mechanism of Action of the Prenyltransferase MoeN5. Issue 15 (8th March 2016) - Zhang, Lilan; Chen, Chun‐Chi; Ko, Tzu‐Ping; Huang, Jian‐Wen; Zheng, Yingying; Liu, Weidong; Wang, Iren; Malwal, Satish R.; Feng, Xinxin; Wang, Ke; Huang, Chun‐Hsiang; Hsu, Shang‐Te Danny; et al.
Abstract: The structure of MoeN5, a unique prenyltransferase involved in the biosynthesis of the antibiotic moenomycin, is reported. MoeN5 catalyzes the reaction of geranyl diphosphate (GPP) with the cis ‐farnesyl group in phosphoglycolipid5 to form the (C25 ) moenocinyl‐sidechain‐containing lipid7 . GPP binds to an allylic site (S1) and aligns well with known S1 inhibitors. Alkyl glycosides, glycolipids, can bind to both S1 and a second site, S2. Long sidechains in S2 are "bent" and co‐locate with the homoallylic substrate isopentenyl diphosphate in other prenyltransferases. These observations support a MoeN5 mechanism in which5 binds to S2 with its C6–C11 group poised to attack C1 in GPP to form the moenocinyl sidechain, with the more distal regions of5 aligning with the distal glucose in decyl maltoside. The results are of general interest because they provide the first structures of MoeN5 and a structural basis for its mechanism of action, results that will facilitate the design of new antibiotics. Abstract : The structure of MoeN5, a unique prenyltransferase essential for the biosynthesis of the antibiotic moenomycin, was determined by using a fusion‐tag approach. MoeN5 catalyzes the production of a (C25 ) moenocinyl trisaccharide (1 ), and the structures provide insight into the binding of substrates in the S1 and S2 sites. These results provide a structural basis for the mechanism of action of MoeN5, and could facilitate the design of new antibiotics.